The role of matrix, fiber, and interface (New York, 1992)
This book focuses on the mechanical properties and structural integrity of composites and prediction of their performance. It integrates and discusses four important topics: matrix resin chemistry, role of the fiber, interactions between fiber and matrix, and special applications of composites
Keywords: composite materials,fibrous composites,polymeric composites